Level of Understanding of Nutrition Needs and Dehydration Status of Mataram Soccer Academy Students - BAUSAD, ANDI ANSHARI (Journal of Physical and Outdoor Education, 2023)
This study aims to measure the level of understanding of the nutritional status and dehydration status of Mataram Soccer Academy students. Based on descriptive analysisdata obtained, 18 athletes namely the aspect of knowledge with a value of 584 points with an average of 32.4% and aspects of attitude/behavior with a value of 447 points with an average of 24.8%.The level of understanding of the nutritional intake needs of Mataram Soccer Academy students in the knowledge aspect is in the very good category at 81%, in the attitude/behavior aspect it is in the good category at 68.89%, and overall is in the good category at 75.27%. 9 out of 18 Mataram Soccer Academy students are well hydrated or 50% of the total number of students are not dehydrated, then 9 of the next 18 students are not properly hydrated or 50% of the total number of students are mildly dehydrated, and 0 out of 18 students experience a lack of fluids or 0% of the total number of students experiencing severe dehydration. If you look at the assessment criteria for the results of data processing, the dehydration status of Mataram Soccer Academy students is included in the (enough) category with an average percentage of 50%. Understanding the nutritional intake needs of Mataram Soccer Academy students based on the knowledge aspect is in the very good category, this illustrates that Mataram Soccer Academy students already understand about fulfilling nutritional intake but not in practice in other words Mataram Soccer Academy students already understand enough but in application students are still not enough.